Sensory acceptability of value added cookies incorporated with Tinospora cordifolia (TC) stem powder; improvement in nutritional properties and antioxidant potential - Tyagi, Prachi (J Food Sci Technol, 2020)
Tinospora cordifolia (TC) is regarded nature’s treasure as it is salutary in various ways to the human health in ayurvedic and vedic scriptures. The TC stem creeping on neem tree (Azadirachta indica) are considered best for medicinal use. Present study was carried out to develop functional food as cookies by incorporating the TC stem powder. Functional cookies were prepared by incorporating 2%, 4%, 8%, 10% and 12% of TC stem powder and admissibility was decided on the basis of sensory evaluation to get the optimized cookies (TCC). Further physical parameters (L*, a* and b* color value and spread ratio) were analyzed. TC, TCC and control cookies without TC were evaluated for nutritional composition and antioxidant potential [antioxidant assays: 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing power (FRAP) and nitric oxide (NO), total polyphenolic content and total flavonoid content]. Results showed that with increase in TC addition from 0 to 12% in cookies there was decreases in the sensory parameters and maximum admissible concentration was up to 8% of TC, hence optimized at this level. Incorporation of TC in cookies resulted in increase in b(*) value, protein, moisture, total ash, iron, copper, zinc and antioxidant potential, whereas the fat content decreases. Developed cookies proved to be better than standard control cookies with respect to functional properties.